Comportamiento agronómico de cinco hortalizas de hojas con tres abonoso Orgánicos en la quinta huertos familiares - Santo Domingo de los Tsáchilas. - Ovalle Correa, Guido Alberto (2013)
This research was conducted in the Fifth Allotment Gardens Lot 44-pass located in Santo Domingo - Quito Km 1 left margin belonging to the province of Santo Domingo de Los Tsáchilas. Its geographical location is 0 ˚ .2 ̛5 degrees south latitude and 79 ˚ 15 west longitude, with an altitude of 625 meters. Design We used a randomized complete block (RCBD) in factorial arrangement with five vegetables with three organic fertilizers and three replicates plus a control. In treating humus + water hyacinth variables leaf length (cm), leaf number, weight (g) and yield (tha-1) got a big turnip average with 46.02 (cm), 18.07, 1087.73 (g) and 10.88 (t ha-1) in your order. The results were: In the variables of chard, vermicompost treatment + water hyacinth, with 1.06 (tha-1) achieved its profitability. In the variable broccoli stem diameter, vermicompost treatment + water hyacinth showed the highest average with 2.70 cm. Set to the leaf length, leaf width, weight and cost of green cabbage worm compost treatment + water hyacinth had the highest average with 26.60 (cm), 29.87 (cm), 1388.00 (g) and 13.88 (t ha-1) with respect to the stem diameter, vermicompost treatment received the highest average stem diameter with 2.51 cm. In vermicompost treatment + water hyacinth in weight and performance variables cabbage achieved their highest average with 665.33 (g) and 6.65 (t ha-1) in your order. In the economic analysis Chard with Humus treatment + water hyacinth, with 23.65 USD got the most useful and best benefit / cost ratio of 0.46.